2017
DOI: 10.1007/s10517-017-3871-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Matrix Metalloproteinases Genes MMP1, MMP2, MMP3, and MMP7 and the Risk of Varicose Veins of Lower Extremities

Abstract: We studied the effects of single nucleotide polymorphisms in the promoter regions of matrix metalloproteinase genes rs1799750 (-1607dupG) MMP1, rs243865 (C-1306T) MMP2, rs3025058 (-1171dupA) MMP3, and rs11568818 (A-181G) MMP7 on the risk of varicose vein of the lower extremities in ethnical Russians, residents of the Russian Federation. We genotyped 536 patients with this pathology and 273 healthy participants without history of chronic venous disease. Association was examined using logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thus, the table "Polymorphic variants/mutations of candidate genes and their associations with chronic venous disease" shows not only the gene, the type of mutation/single nucleotide polymorphism (SNP) and the reference to the article, but also the sample size and the degree of this association, which is decisive for the significance of this association. In the studies performed in our laboratory, it has been shown that, for example, for polymorphic variants of genes AGGF1 (rs13155212, rs7704267) [13] , MTHFR (rs1801133) and MTR (rs1805087) [14] , no associations with the risk of VVD in ethnic Russians were found. There were also no associations found for regulatory SNPs of matrix metalloproteinase genes MMP1 (rs1799750), MMP2 (rs243865), MMP3 (rs3025058) and MMP7 (rs11568818) [15] , whereas the rare rs1800562 A allele in the HFE gene leading to the accumulation of iron in the patient's tissues [16] and polymorphic variants rs1035550 C>T and rs34221221 T>C of the transcription factor FOXC2 gene [17] were associated with an increased risk of VVD.…”
Section: Genetic Association Studies On Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 91%
“…Thus, the table "Polymorphic variants/mutations of candidate genes and their associations with chronic venous disease" shows not only the gene, the type of mutation/single nucleotide polymorphism (SNP) and the reference to the article, but also the sample size and the degree of this association, which is decisive for the significance of this association. In the studies performed in our laboratory, it has been shown that, for example, for polymorphic variants of genes AGGF1 (rs13155212, rs7704267) [13] , MTHFR (rs1801133) and MTR (rs1805087) [14] , no associations with the risk of VVD in ethnic Russians were found. There were also no associations found for regulatory SNPs of matrix metalloproteinase genes MMP1 (rs1799750), MMP2 (rs243865), MMP3 (rs3025058) and MMP7 (rs11568818) [15] , whereas the rare rs1800562 A allele in the HFE gene leading to the accumulation of iron in the patient's tissues [16] and polymorphic variants rs1035550 C>T and rs34221221 T>C of the transcription factor FOXC2 gene [17] were associated with an increased risk of VVD.…”
Section: Genetic Association Studies On Varicose Vein Pathogenesis-an Overviewmentioning
confidence: 91%
“…We must emphasize that after the visit of a Vascular Specialist the prescription of venoactive drugs and graduated compression stockings rose 3-fold. This clearly shows the importance of being taken in charge by a vascular specialist (6, [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In further agreement with advocating a more individualised approach to management of CVD, the specialists also found consensus on statement 10 regarding the utility of identifying genetic polymorphisms that may affect progression of CVD. Indeed, several polymorphisms have been identified that appear to stratify with disease, notably HFE p.C282Y as well as those in metalloproteases [57][58][59][60]. Other researchers have proposed that a genetic risk score might be useful in distinguishing patients at risk for more severe disease [61].…”
Section: Conservative Therapymentioning
confidence: 99%